2007
DOI: 10.3354/meps07140
|View full text |Cite
|
Sign up to set email alerts
|

Migratory behaviour of Atlantic cod Gadus morhua: natal homing is the prime stock-separating mechanism

Abstract: KEY WORDS: Cod · Data storage tag · DST · Light geolocation · Natal homing Resale or republication not permitted without written consent of the publisherCod Gadus morhua migrations can be assessed with archival tags, which store measurements of temperature, pressure (depth) and light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 28 publications
7
122
0
Order By: Relevance
“…However, it is somewhat surprising that there was not a more marked seasonality, given that the timing of cod spawning is thought to occur mainly over a few months in early spring (Cushing & Dickson 1976). One possibility is that the movements we recorded might not only be associated with migration to spawning grounds before the spawning season in January and February but might also reflect repositioning onto new feeding grounds once spawning is over (Turner et al 2002, Wright et al 2006, Svedäng et al 2007). Similar spatial dynamics are shown in plaice (Hunter et al 2004a), and are typical of migratory fish species that aggregate on spatially restricted spawning grounds before dispersal to widespread feeding grounds (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is somewhat surprising that there was not a more marked seasonality, given that the timing of cod spawning is thought to occur mainly over a few months in early spring (Cushing & Dickson 1976). One possibility is that the movements we recorded might not only be associated with migration to spawning grounds before the spawning season in January and February but might also reflect repositioning onto new feeding grounds once spawning is over (Turner et al 2002, Wright et al 2006, Svedäng et al 2007). Similar spatial dynamics are shown in plaice (Hunter et al 2004a), and are typical of migratory fish species that aggregate on spatially restricted spawning grounds before dispersal to widespread feeding grounds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is great concern over the decline in stock sizes for the cod Gadus morhua, particularly in the North Sea and the Grand Banks in the last 20 yr (Myers et al 1997, Christensen et al 2003, Horwood et al 2006. While the understanding of cod movements is increasing (Turner et al 2002, Robichaud & Rose 2004, Neat et al 2006, Svedäng et al 2007, the development of a mechanistic understanding of these movements may allow the availability of cod fishing potential at different spatial and temporal scales (O'Brien et al 2000). Similarly, information on cod depth utilisation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a minor fraction (13%) of the total recaptures were made by researchers, and evidence from other studies suggests that fishing rates by commercial and recreational fishermen were likely to be relatively high elsewhere along the Norwegian Skagerrak coast, as well as offshore in the Skagerrak, Kattegat, and N orth Sea. Previous tagging studies in the eastern Skagerrak and Kattegat have reported recapture and reporting rates by commercial fishers ranging from 20 to 66% depending on region and year (Robichaud & Rose 2004, Svedäng et al 2007). There is no reason to believe that reporting rates for the current study should have been lower.…”
Section: Discussionmentioning
confidence: 99%
“…Mar Ecol Prog Ser 410: [177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195] 2010 the importance of processes that limit dispersal and promote self-replenishment of local populations, such as sedentary adult life history strategies (Robichaud & Rose 2004, Howell et al 2008, spawning site fidelity (Taggart 1997), natal homing (Thorrold et al 2001, Svedäng et al 2007), egg and larval retention (Jones et al 1999, 2005, Bradbury et al 2008) and local adaptation (McIntyre & Hutchings 2003, Conover et al 2006, Hutchings et al 2007). The implications of such fine-scale population structure are important for effective management (Palumbi 2003, Bradbury et al 2008, Reiss et al 2009).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%